(3GdbVGA GdEOGQj heLdS ThQi GdOhdI GddHfGfjs - (3YHO GdZfj YHO Gddg(B, (3HSjhfjs ((3HjQhJ(B:s (3GdOGQ GdLGeYjI,s, 2001)
(3eHOC GdeTQhYjI hJfXje GdbVGA GdGOGQj(B: (3eHOC GdeTQhYjI, GdQbGHI Ydi CYeGd GdGOGQI hJfXje GdbVGA GdGOGQj, fWGb GNJUGU GdbVGA GdGOGQj GddHfGfj(B: (3NQhL GdCYeGd GdJTQjYjI hGdGYeGd GdbVGFjI ef GNJUGU GdbVGA GdGOGQj, GNJUGU GdbVGA GdGOGQj HGdefGRYGJ GdGOGQjI, JfGRY GdGNJUGU Hjf GdbVGA GdYGOj, OYhi GdGdZGA Ch GdGHWGd(B: (3TQhW bHhd OYhi GdGdZGA, CSHGH GdGdZGA Ch GhLg GdGHWGd, CUhd GdJbGVj hGLQGAGJ GdeQGLYI CeGe GdbGVj GdGOGQj GddHfGfjs
Keywords: (3GdQbGHIs; (3GdbGfhf GdEOGQj(B- (3dHfGf s; (3GdbVGA GdGOGQjs